플라이애쉬를 이용하여 제조된 인공경량골재를 이용한 황화수소의 제거 연구 - 김낙주(Nack Joo Kim); 조호영(Ho Young Cho); 김석구(Seog Ku Kim); 강성원(Sung Won Kang); 민수홍(Soo Hong Min Yun); 이태윤(Tae Yoon Lee) (Daehan hwan'gyeong gonghag hoeji, 2006)
본 연구에서는 산업폐기물인 플라이애쉬를 이용하여 악취물질인 황화수소를 효과적으로 제거하기 위해 입자형태로 제조하여 다양한 실험조건 하에서 제거효과를 관찰하였다. 입자형태로 제조하기 위한 최적조건을 선정하기 위해 플라이애쉬 함량, 시멘트 함량, 함수비, 발포제의 양을 변화시켜 공시체를 제조하였으며, 각 공시체에 대해 비중, 흡수율, 압축강도의 값을 측정하였다. 이들 측정값과 실험 시 편의사항을 고려하여 악취제거 실험에 사용될 시료를 선정하였으며, 회분식 및 컬럼실험을 통해 황화수소의 제거양상을 측정하였다. 본 연구조건 하에서의 황화수소 제거율은 사용된 플라이애쉬 입자의 양과 정비례의 관계를 보여주었으며, 수분 첨가 시 황화수소 제거율이 증가하는 것을 확인하였다. Artificial aggregates made by coal fly ash that is classified as an industrial by-product was tested to oxidize hydrogen sulfide under various testing conditions. For the determination of optimum condition for converting coal fly ash to aggregates, specimens were prepared by varying ratio of fly ash, cement, water content, and foaming agent. These specimens were tested to determine specific gravity, water absorption, and compressive strength. Specimens, which were used for the removal of hydrogen sulfide, were selected based on the measured specific gravity, water absorption, and compressive strength. Tests for hydrogen sulfide removal were performed via batch and column tests. Under the testing conditions used in this study, removal rates of hydrogen sulfide were linearly proportional to amounts of coal fly ash, and further increased when water was added. KCI Citation Count: 2